Assessing Public Expenditures in Small Towns: Beyond Roads and Fire Engines. (June 2017) - Helpap, David J.
Large, urban governments often provide a tremendous variety of public goods, while the expenditures of small communities usually address basic needs such as fire protection and road maintenance. However, certain small local governments dedicate significant public resources to recreation, culture, and public health services, among others. This research examines the variation in services provided by these smaller, often overlooked governments. Differences are explained, at least partially, by various community characteristics, location, and capacity. For the millions of people who reside in these communities, the findings illustrate why variations exist and what, potentially, can be done to alter expenditure levels.